Fatty acids profiles and estimation of the biodiesel quality parameters from Rhodotorula spp. from Antarctica - Viñarta, Silvana Carolina; Angelicola, María Virginia; Van Nieuwenhove, Carina Paola; Aybar, Manuel Javier; Castellanos, Lucia Ines (Biotechnology Letters)
Oleaginous yeasts are a renewable and alternative source of oil for third-generation biodiesel. This work aimed to evaluate the effects of glucose concentration (30?100 g/L) on growth, lipid synthesis, and fatty acids (FA) profile of three Rhodotorula spp. (R. glacialis R15, R. glutinis R4, and R. glutinis R48) isolated from Antarctica, and estimate the key quality parameters of the biodiesel produced by yeasts to confirm their potential as feedstocks for third-generation biodiesel synthesis. Yeasts accumulated 50?69.5% of lipids (w/w) under nitrogen-limitation and glucose-excess (C/N = 40?133). Glucose concentration increase influenced positively lipid accumulation (69.5% w/w) and FA profile of R. glacialis R15. Lipid accumulation (53% on average) of R. glutinis strains was not significantly affected by glucose concentration; content of saturated (⁓30%) and polyunsaturated FA (⁓29?30%) was slightly influenced. FA profiles of lipids synthesized by R15, R4, and R48 are similar to vegetable oils used in biodiesel industry with C16 and C18 FA (95?99%) as the major components, and contain mainly oleic (C18:1), palmitic (C16:0), and linoleic (C18:2) acids, which are suitable for biodiesel synthesis. Estimated fuel properties for biodiesel produced by R15, R4, and R48 satisfied all the criteria established by ASTM D6751 and EN 14214 with good cetane number, iodine value, and oxidation stability. An improvement in biodiesel quality of R15 was observed with the glucose increase. The best global properties of biodiesel from R4 were obtained with 30 g L-1 of glucose. Rhodotorula spp. from Antarctica are promising candidates for third-generation biodiesel synthesis. Fil: Viñarta, Silvana Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Instituto Superior de Investigaciones ...